An evaluation on potential anti-oxidant and anti-inflammatory effects of Crocin - Bastani, Sepideh; Vahedian, Vahid [UNESP]; Rashidi, Mohsen; Mir, Amirabbas; Mirzaei, Sepideh; Alipourfard, Iraj; Pouremamali, Farhad; Nejabati, Hamidreza; kadkhoda, Jamileh; Maroufi, Nazila Fathi; Akbarzadeh, Maryam (Elsevier, 2022)
Crocin, an active ingredient derived from saffron, is one of the herbal components that has recently been considered by researchers. Crocin has been shown to have many anti-inflammatory and antioxidant properties, and therefore can be used to treat various diseases. It has been shown that Crocin has a positive effect on the prevention and treatment of cardiovascular disease, cancer, diabetes, and kidney disease. In addition, the role of this substance in COVID-19 pandemic has been identified. In this review article, we tried to have a comprehensive review of the antioxidant and anti-inflammatory effects of Crocin in different diseases and different tissues. In conclusion, Crocin may be helpful in pathological conditions that are associated with inflammation and oxidative stress.
Keywords: Anti-inflammatory; Anti-oxidant; Cancer; Covid19; Crocin